Multi-level convergence challenges of regional economic development - V. V. Stroev (Вестник университета, 2023)
This study is devoted to the analysis of convergence in the economic development of regions, and these aspects are considered in the article in conjunction with the general trend of departure from economic globalization and transition to a new regionalism. The general trend of the new regionalism in the modern world, the manifestation of intraregional imbalances not only at the level of the integration association of countries, but at the intra-country level are considered. It is established that a significant motive in favor of regionalization is the strengthening of relations and strategic partnership between “friendly” countries, which changes the previously established models of international economic cooperation, and focuses on regional priorities of socio-economic development. The analysis of regional convergence has shown that such convergence has a historical trend towards a slowdown, which is generally manifested at the international and domestic levels, which is partly due to heterogeneous models of regional growth. In the future, countries and regions will need new mechanisms to adapt to crises and turbulence of the global economy.